2022
DOI: 10.1080/20002297.2022.2107691
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis-Helicobacter pylori co-incubation enhances Porphyromonas gingivalis virulence and increases migration of infected human oral keratinocytes

Abstract: Background Porphyromonas gingivalis is part of the subgingival biofilm and a keystone species in the development of periodontitis. Interactions between P.gingivalis and other bacteria in biofilms have been shown to affect bacterial virulence. Helicobacter pylori also inhabits the subgingival biofilm, but the consequences of interactions there with P.gingivalis remain unknown. Here, we investigated how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Escape of neutrophils and killing by destructive macrophages paves the way for the long-term persistence of Pseudomonas gingivalis . Then down-regulates the differentiation and development of adaptive immune cells: The ability to manipulate T-cell differentiation and immune responses provides for the survival of Pseudomonas gingivalis in the host ( Soto et al., 2022 ). Low-grade inflammation induced by the innate immune system occurs under the control of the adaptive immune system, and if the immune system is compromised, the presence of bacteria at the site of infection may lead to systemic inflammation, thereby exacerbating insulin resistance ( Harding et al., 2017 ; Ganz et al., 2022 ).…”
Section: Pathogenesis Of Insulin Resistance Caused By P Gin...mentioning
confidence: 99%
“…Escape of neutrophils and killing by destructive macrophages paves the way for the long-term persistence of Pseudomonas gingivalis . Then down-regulates the differentiation and development of adaptive immune cells: The ability to manipulate T-cell differentiation and immune responses provides for the survival of Pseudomonas gingivalis in the host ( Soto et al., 2022 ). Low-grade inflammation induced by the innate immune system occurs under the control of the adaptive immune system, and if the immune system is compromised, the presence of bacteria at the site of infection may lead to systemic inflammation, thereby exacerbating insulin resistance ( Harding et al., 2017 ; Ganz et al., 2022 ).…”
Section: Pathogenesis Of Insulin Resistance Caused By P Gin...mentioning
confidence: 99%
“…The total proportion of periodontal pathogens in oral H. pylori -positive subgingival plaque samples was higher than that in H. pylori -negative samples [ 40 ], indicating that oral H. pylori infection may promote periodontal disease by altering the microecology. Preincubation of Porphyromonas gingivalis ( P. gingivalis ) with H. pylori affects P. gingivalis virulence, including biofilm formation, bacterial internalization into oral keratinocytes, and hemagglutination, indicating that the direct interaction between P. gingivalis and H. pylori in subgingival plaque may increase the severity or progression of periodontitis [ 41 ]. In addition, the expression of periodontitis-related protein Wnt5a and cytokines IL-8, IL-6, and INF-γ was significantly increased after cagA + H. pylori stimulated the human leukemia mononuclear cell line, suggesting that H. pylori can aggravate inflammation progression [ 40 ].…”
Section: The Evidence For the Persistent Survival Of Oral H...mentioning
confidence: 99%
“…H. pylori may promote the severity of periodontitis. Preincubation of P. gingivalis with H. pylori enhanced P. gingivalis virulence, including biofilm formation, bacterial internalization into oral keratinocytes, and hemagglutination [ 41 ]. In addition, the role of F. nucleatum in the survival of H. pylori is worthy of further investigation, as H. pylori -negative chronic gastritis patients were reported to have lower levels of F. nucleatum in saliva than healthy subjects [ 124 ].…”
Section: The Synergistic Interactions Of Oral H Pylori ...mentioning
confidence: 99%
“…Furthermore, research in our laboratory has shown that P. gingivalis can also interact with Helicobacter pylori, also present in the oral bacterial community. This interaction results in increases in the virulence of P. gingivalis and the expression of RgpB gingipain and is directly associated with the enhanced migration of infected cells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Co-culture models are vital for studying interactions between prokaryotic and oral eukaryotic cells, unraveling the pathogenesis of polymicrobial diseases, such as oral conditions [24]. These models enable researchers to explore co-culture dynamics, revealing effects on bacterial gene expression and virulence [15,16,19,25]. In a previous study, it was demonstrated that LPS purified from P. gingivalis co-cultured with F. nucleatum increased the expressions and secretions of IL-1β, IL-6, and IL-8 in monocytes when compared to the effect of purified LPS derived from monocultured P. gingivalis [25].…”
Section: Introductionmentioning
confidence: 99%